2014
DOI: 10.2147/cia.s40154
|View full text |Cite
|
Sign up to set email alerts
|

Increasing complexity: which drug class to choose for treatment of hypertension in the elderly?

Abstract: Treatment of hypertension in the elderly is expected to become more complex in the coming decades. Based on the current landscape of clinical trials, guideline recommendations remain inconclusive. The present review discusses the latest evidence derived from studies available in 2013 and investigates optimal blood pressure (BP) and preferred treatment substances. Three common archetypes are discussed that hamper the treatment of hypertension in the very elderly. In addition, this paper presents the current rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 122 publications
0
13
0
Order By: Relevance
“…Similarly, guidelines are conflicting regarding the optimal blood pressure targets and choice of blood pressure-lowering agents for older patients with CKD. 37 Given the heterogeneity in patient characteristics and preferences, it is important to consider which outcomes matter most for individual patients when making decisions about therapy. For example, some patients may care most about maximizing longevity, whereas others may consider quality of life and daily functioning equally important.…”
Section: Clinical and Public Health Implications Of Ckd In Older Adultsmentioning
confidence: 99%
“…Similarly, guidelines are conflicting regarding the optimal blood pressure targets and choice of blood pressure-lowering agents for older patients with CKD. 37 Given the heterogeneity in patient characteristics and preferences, it is important to consider which outcomes matter most for individual patients when making decisions about therapy. For example, some patients may care most about maximizing longevity, whereas others may consider quality of life and daily functioning equally important.…”
Section: Clinical and Public Health Implications Of Ckd In Older Adultsmentioning
confidence: 99%
“…The number of elderly patients with essential hypertension is increasing annually at a rapid rate worldwide [1, 2]. Recent data from the National Health and Nutrition Examination Survey indicate that 70% of older adults have hypertension [3].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning concomitant cardiovascular medications, beta-blockers, angiotensin-conversion-enzyme inhibitors, angiotensin-receptor-blockers, nitrate derivatives, diuretics, cardiac glycosides, other antiarrhythmic drugs, and hypolipidemic drugs (including statins) were more commonly prescribed in VKAG than in noVKAG. This result can be explained by the fact that cardiovascular diseases were more frequent in the VKAG [ 7 , 29 , 30 , 31 ]. A study showed a risk of overdose for phenprocoumon and acenocoumarol in cases of concomitant statins use [ 32 ].…”
Section: Discussionmentioning
confidence: 99%